Reviewing the use of corticosteroids in bronchopulmonary dysplasia - Fernanda Aparecida de Oliveira Peixoto; Paulo Sérgio Sucasas Costa (Elsevier, 2016)
Abstract Objective: Review the risks and benefits of postnatal corticosteroid use for the treatment of bronchopulmonary dysplasia, considering that there is not a more effective therapy. Data sources: The literature review was carried out in the BIREME database, using the terms "bronchopulmonary dysplasia and corticosteroid" in the LILACS, IBECS, MEDLINE, Cochrane Library, and SciELO databases, selecting the most relevant articles on the subject, with emphasis on recent literature published in the last five years. Summary of the data: In preterm infants, bronchopulmonary dysplasia is still a common problem and remains without a specific therapy, despite knowledge of the several risk factors. The treatment essentially consists of supportive measures, but in the past, corticosteroids were widely used, as they are the only medications that have an impact on disease progression. However, the emergence of cerebral palsy associated with the indiscriminate use of corticosteroids has prevented the prescription of this drug in the last 15 years. Since then, no new measures have been taken, and the incidence of the disease tended to increase during this period, creating the need for a review of corticosteroid use and, possibly, more restricted indications. Conclusions: The association between risks and benefits of corticosteroid use in preterm infants needs to be considered due to the fact that some infant subpopulations may show more benefits than risks, such as those using mechanical ventilation with difficult weaning.